Path dependence in national systems of production and "self discovery" of environmental technologies in the EU 28 countries - Andreas Reinstaller; Peter Reschenhofer (WWWforEurope, 2015)
The development of "green" industries is commonly seen as a necessary even though not sufficient condition for the transition towards ecologically sustainable paths of economic development. It is also a recurrent view that pro-active and successful policy action in this domain will not only promote sustainable development but also secure competitive advantage of successful countries in these industries. However, a complex constellation of path-dependencies in systems of production and (negative) externalities constrain the emergence and expansion of environmental technologies. This paper presents evidence that path-dependencies in systems of production have a dual role in the development of new industries. They are not only a source of structural lock-in, but also a potential starting point for new developments. The paper shows that factors causing path dependence in systems of production are also an important source of competitiveness both for all traded commodities and for environmental technology industries. Hence, policies supporting the emergence of industries producing environmental technologies should try to exploit this mechanism. Drawing on this evidence a counterfactual analysis is carried out to investigate potential trajectories of development of the EU28 countries in the environmental technologies. The results indicate that some countries that up to recent times have been pioneers in environmental technologies may lose their strong position in these technologies. In other countries instead new strengths in environmental technologies have the potential to emerge, as some environmental technologies can draw on untraded interdependencies that have not been brought to full fruition so far.
Keywords: O31; O32; 330; Product space; local capabilities; related diversification; competitiveness